Widespread extracellular electron transfer pathways for charging microbial cytochrome OmcS nanowires via periplasmic cytochromes PpcABCDE - Portela, Pilar C. (2024)
We thank Gary Brudvig for advice on spectroelectrochemistry measurements and M. Gubermann-Pfeffer for help with ZDOCK. This research was supported by the National Defense Science and Engineering Graduate Fellowship (to C.C.S.), the Human Frontier Science Program award no. RGP017/2023 (to N.S.M. and C.A. S.), NSF CAREER award no. 1749662 (to N.S.M.), the NSF-ANR award no. 2210473 (to N.S.M.), and the National Institutes of Health (NIH) Director’s New Innovator award (1DP2AI138259-01 to N.S.M.). Publisher Copyright: © The Author(s) 2024